Case Report: A case of ruptured renal epithelioid angiomyolipoma leading to the diagnosis of TSC2/PKD1 contiguous gene syndrome - Akiba, Takato; Shimada, Shino; Ikegami, Michiaki; Nishizaki, Naoto; Hashizume, Akane; Nozaki, Taiji; Nagashima, Yoji; Tsujimura, Akira; Nakazawa-Tanaka, Nana; Miyano, Go; Takahashi, Ken; Shoji, Hiromichi (Frontiers in Pediatrics, 2026)
BackgroundTuberous sclerosis complex (TSC) is frequently complicated by renal lesions, including angiomyolipoma (AML), renal cysts, and renal cell carcinoma (RCC). Large deletions involving adjacent TSC2 and PKD1 genes cause TSC2/PKD1 contiguous gene syndrome (PKDTS), which carries a risk of early renal decline. Epithelioid AML (eAML), to the best of our knowledge, has not been previously reported in children with PKDTS.Case presentationA 13-year-old boy with hypomelanotic macules and facial angiofibromas presented with acute abdominal pain and fever; CT revealed a ruptured heterogeneous 5-cm right renal cystic, and multiple cysts. Robot-assisted partial nephrectomy confirmed epithelioid angiomyolipoma (eAML) via pathology and immunohistochemistry (cathepsin K+, CD10/p53 partial+, others negative). Neuroimaging and ophthalmology revealed TSC features; chromosomal microarray identified an ∼882-kb 16p13.3 deletion encompassing TSC2/PKD1, diagnosing PKDTS.ConclusionsPKDTS may manifest in childhood as an eAML rupture. In pediatric TSC, eAML or RCC should not be excluded based on age. Atypical findings (e.g., calcification or necrosis) warrant early biopsy; non-diagnostic sequencing requires copy-number analysis (e.g., chromosomal microarray) to detect TSC2 deletions in TSC-featured patients and multiple renal cysts.